The Crisis of Islamic Identity and its Relation to Extremism and Terrorism - Sahli , Bahiah (Nama Journal of Islamic Sciences and Humanities, 2023)
This research aims to study the crisis of Islamic identity and its relation to extremism and terrorism. It is divided into an introduction and three chapters. The first chapter discussed the identity of the Islamic nation. The second chapter deals with the concept of extremism and terrorism and their causes. The third chapter discussed the terrorist extremist nature. It concluded that it is not possible to assert the unity of the Islamic identity in the circumstances of the events that the Islamic nation is going through after the emergence of the sects. Extremism and terrorism are the result of the internal gap in the Islamic nation, along with other factors. In addition, the crisis of the Islamic identity has led to disturbances in the collective perceptions of Muslims.